THE STRUGGLE OF MUTANT HUMAN AS A GROTESQUE CHARACTERS IN FUTURAMA (1999) - Lutfi Fachrulrozi; Dian Nurrachman; Bunyamin Faisal Syarifudin (Saksama, 2022)
This study examined the struggle of the mutant human as a grotesque characters in Futurama animated series. The grotesque theory that is being used are from Bakhtin, Bloom, Haar and Thomson to analyze the mutant character in the story. The aims of this study was to identify the struggle of the mutant caused by their grotesque body as well as how the grotesque body has impacted their life in the story. The study examines a couple of material mainly scenes and the visual of the series. it does this using a qualitative research methodology. In order to be interpreted, the researchers specify the research into two section, the first section is analyzing Leela’s struggle as a grotesque character because she was one of the main cast of the character, and the second one is analyzing the mutant human as a whole. The finding demonstrate that all of the mutant kind faced struggle caused by their body deformity, those struggle are usually in the form of discrimination, prejudice and degradation.